Homozygous Familial Hypercholesterolemia Patients With Identical Mutations Variably Express the LDLR (Low-Density Lipoprotein Receptor): Implications for the Efficacy of Evolocumab - Thedrez, Aurélie; Blom, Dirk J.; Ramin-Mangata, Stéphane; Blanchard, Valentin; Croyal, Mikaël; Chemello, Kévin; Nativel, Brice; Pichelin, Matthieu; Cariou, Bertrand; Bourane, Steeve; Tang, Lihua; Farnier, Michel; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2018)
OBJECTIVE—Evolocumab, a PCSK9 (proprotein convertase subtilisin kexin type 9)–neutralizing antibody, lowers low-density lipoprotein cholesterol (LDL-C) in homozygous familial hypercholesterolemic (HoFH) patients with reduced LDLR (low-density lipoprotein receptor) function. However, their individual responses are highly variable, even among carriers of identical LDLR genetic defects. We aimed to elucidate why HoFH patients variably respond to PCSK9 inhibition. APPROACH AND RESULTS—Lymphocytes were isolated from 22 HoFH patients enrolled in the TAUSSIG trial (Trial Assessing Long Term Use of PCSK9 Inhibition in Subjects With Genetic LDL Disorders). Ten patients were true homozygotes (FH1/FH1) and 5 identical compound heterozygotes (FH1/FH2). Lymphocytes were plated with or without mevastatin, recombinant PCSK9 (rPCSK9), or a PCSK9-neutralizing antibody. Cell surface LDLR expression was analyzed by flow cytometry. All HoFH lymphocytes had reduced cell surface LDLR expression compared with non-FH lymphocytes, for each treatment modality. Lymphocytes from FH1/FH2 patients (LDLR defective/negative) displayed the lowest LDLR expression levels followed by lymphocytes from FH1/FH1 patients (defective/defective). Mevastatin increased, whereas rPCSK9 reduced LDLR expression. The PCSK9-neutralizing antibody restored LDLR expression. Lymphocytes displaying higher LDLR expression levels were those isolated from patients presenting with lowest levels of LDL-C and apolipoprotein B, before and after 24 weeks of evolocumab treatment. These negative correlations remained significant in FH1/FH1 patients and appeared more pronounced when patients with apolipoprotein E3/E3 genotypes were analyzed separately. Significant positive correlations were found between the levels of LDLR expression and the percentage reduction in LDL-C on evolocumab treatment. CONCLUSIONS—Residual LDLR expression in HoFH is a major determinant of LDL-C levels and seems to drive their individual response to evolocumab.